MAPPING READING EXERCISES IN ENGLISH TEXTBOOK FOR ELEVENTH GRADE STUDENTS BASED ON HOTS - Johannes Jefria Gultom; Maryana Sitinjak (BAHAS, 2020)
AbstractThis study is about the cognitive level of reading exercises in an English textbook for eleventh grade students based on Revised Bloom’s Taxonomy. The objective of the study was to investigate the distribution of the higher order thinking skills in the reading exercises of students’ textbooks entitled Bahasa Inggris which is published by the Ministry of Education and Culture. This study was conducted by using descriptive qualitative method. The data of this study were the reading texts’ exercises in the textbook. The result of this study was the reading exercises in Bahasa Inggris textbook covered all of the cognitive levels, they are Remembering (43.90%), Understanding (20.73%), Applying (6.1%), Analyzing (1.83%), Evaluating (1.22%), and Creating (26.22%). Thus, the distribution of higher order thinking skills (analyzing, evaluating, and creating) in the textbook was 29.27%, and for the lower order thinking skills obtained 70.73%. Thus, reading exercises developed in Bahasa Inggris textbook provided Higher Order Thinking Skills questions to students at the eleventh grade.Key words: Higher Order Thinking Skills; Reading Exercises; Revised Bloom’s Taxonomy